Melatihkan Keterampilan Berpikir Kritis Dan Berpikir Kreatif Peserta Didik dengan Model Scientific Critical Creative Thinking - Rusmansyah Rusmansyah; Nurul Huda; Linda Safitri; Heldaniah Heldaniah; Isnawati Isnawati; Mahdian Mahdian (Chemistry Education Department of Education and Teaching Faculty, 2022)
21st-century skills demand that learners have critical thinking and creative thinking skills, which can be used in solving problems in everyday life in chemistry learning activities. The Scientific Critical Creative Thinking (SCCrT) model is one of the constructivist learning models that can train students' critical thinking and creative thinking skills. The purpose of this study was to determine the difference between the critical thinking skills and creative thinking skills of students with the SCCrT model (experimental class) and the Direct Instruction (DI) model (control class) in learning salt hydrolysis material. Quasi-experimental research method with nonequivalent control group design, research sample class XI MIPA SMAN 10 Banjarmasin. The research data were obtained from the test results of learners' critical and creative thinking skills, then analyzed descriptively, qualitatively, and inferentially (with the SPSS program version 25). The results showed that the average critical thinking skills with the SCCrT model were higher than those of the DI model (significance value 0.001 < 0.05). The average creative thinking skills with the SCCrT model are also higher than those of the DI model (significance value 0.002 < 0.05). Thus, the SCCrT model is better than the DI model in training learners' critical thinking and creative thinking skills in learning salt hydrolysis material.